Sonogram Before and After Pyloromyotomy: The Pyloric Ratio in Infantile Hypertrophic Pyloric Stenosis - Yu-Lan Huang; Hung-Chang Lee; Chun-Yan Yeung; Wai-Tao Chen; Chuen-Bin Jiang; Jin-Cherng Sheu; Nien-Lu Wang (Pediatrics and Neonatology)
Sonography is used to diagnose infantile hypertrophic pyloric stenosis, but little information is available about the appearance of postoperative sono-graphs. The purpose of this study was to evaluate the morphology of the pylorus in association with an obstruction before and after pyloromyotomy. Methods: Pyloric length, diameter, muscle thickness and intermuscular space were measured sonographically at diagnosis and daily after pyloromyotomy until discharge in 12 infants with infantile hypertrophic pyloric stenosis. The ratios of pyloric wall thickness and intermuscular space to the entire pyloric diameter were measured. Results: The pylorus still appeared hypertrophied after pyloromyotomy on the sono-grams. The traditional measurement of linear dimensions of the pylorus was not significantly changed from the preoperative values by the time of discharge, except for muscle thickness. The intermuscular space increased from 4.8 ± 0.8 mm preoperatively to 7.3 ± 2.1 mm by postoperative day 3 (p= 0.10). Lowe's pyloric ratio at diagnosis was a mean of 0.32, decreasing to 0.29 on postoperative day 3 and 0.29 on the day of discharge (p = 0.82). The alternative pyloric ratio increased significantly by postoperative day 2 (0.24 ± 0.09 on day 2 vs. 0.11 ± 0.07 preoperatively, p = 0.02). Conclusion: The pyloric ratio appears to be a reliable parameter in evaluating the regression of pyloric stenosis after pyloromyotomy, and also aids in the diagnosis of pyloric stenosis.